RANCANG BANGUN E-TRAINING DEPARTEMENT BERBASIS WEB PADA PT SHIMANO BATAM - Narti Eka Putria (Universitas Putera Batam, 2019)
The development of information technology and its relationship with the business world is something that is always interconnected today. Economic principles adopted in the business world require full support for technological developments in order to face increasingly complex global competition, as well as increasingly dynamic market and consumer demands. HR Training Dept. PT. Shimano Batam is one of the many departments that operate under the management of PT. Shimano Batam. This department is fully responsible for employee training before entering the work area, refreshment, and other training that is more specific in accordance with the work program implemented by the company. The design method used in this study is to use the Unified Modeling Language (UML) with the System Development Life Cycle (SDLC) using the Waterfall model. The results obtained in the form of web-based Deptement e-Training application design at PT Shimano Batam, where the application can facilitate the company in obtaining training information provided by employees quickly and accurately and makes it easy for employees to submit training data reports to the company. This application also means very helpful in the work process, both in terms of quality of work and improving employee morale, so that maximum results are achieved by utilizing resources that can be reduced as little as possible.